Patient preferences for telehealth versus in-person oncology visits. Issue 28 (1st October 2022) - Kumar, Deepika; Gordon, Nancy P.; Neeman, Elad; Zamani, Constanza; Sheehan, Tammy Rene; Martin, Ernesto; Payne, Jessica; Egorova, Olga; Kolevska, Tatjana; Liu, Raymond
Abstract : 386 Background: The COVID-19 pandemic led to rapid adoption of telehealth (video or phone) visit modalities for oncology encounters not requiring in-person visits. We surveyed oncology patients regarding preferences for in-person versus telehealth modalities for different types of clinical encounters. Methods: We surveyed adults who were undergoing treatment at Kaiser Permanente Northern California infusion centers between 11/2021 – 05/2022 using a self-administered questionnaire. Patients were asked about modality preferences for 6 types of clinical discussions, overall advantages and disadvantages of telehealth versus in-person encounters, and barriers to video visit use. Results: A total of 757 patients who completed surveys in English answered questions about visit modality preferences for different types of discussions with their oncologist. Respondents were 63% female, median age 63y, and majority White (61% White, 19% Asian, 11% Latino, 7% Black) and college-educated (28% some college, 45% ≥ bachelor's degree). For the first post-diagnosis discussion, most patients preferred in-person (IP) visits (83%), followed by video visits (27%) and phone visits (18%). For follow-up visits during treatment, patients preferred IP (52%), video (50%) and phone (37%) visits. For discussions of bad news and sensitive topics, IP visits were preferred by 68% and 62%, video visits by 44% and 48%, and phone visits by 32% and 41%, respectively. Good news could come at IP (49%), video (52%) or phone (49%) visits. Approximately 20% of patients had no overall preference for IP versus telehealth visits. However, 58% of patients felt more personally connected with their doctor at IP visits. Patients also had more confidence in IP examinations (73%) and felt IP was easier for showing things (67%) and talking (51%) to the doctor. Patients felt telehealth visits saved them time (72%), reduced infection exposure (64%) and travel issues (45%), were cheaper (38%), and enabled inclusion of more people (28%). Of 24% of patients who felt video visits would be hard, 51% cited poor internet, 41% lack of an adequate device, and 28% difficulty signing on. Conclusions: The majority of oncology patients consider telehealth visits acceptable for most types of clinical discussions, with the exception of the first post-diagnosis visit. Only one-fourth of patients indicated potentially modifiable barriers to video visits. Our results support use of telehealth visits for most types of oncology encounters.